THE EFFECTIVENESS OF PUBLIC SERVICES: PRESCHOOL EDUCATION SERVICES IN THE KOMI REPUBLIC - Bolshakova, Julia; Mikhalchenkova, Natalya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article analyzes the tasks of implementing the national project "Education" in the region using the example of the Komi Republic. The article examines the conditions for the implementation of a national education project based on the example of the public servant “preschool education”. Based on monitoring indicators of the provision of pre-school education for children aged 1 to 6 years old in educational institutions in the Komi Republic, an assessment is made of the process of providing services by local authorities. The positive dynamics of the provision of public services in terms of the availability of preschool education in the territory of the Komi Republic is revealed. This indicator is ensured by the construction, re-equipment of premises in existing preschool educational institutions, the redemption of premises for placement of nursery groups, as well as by the development of varied forms of preschool education: groups for short-term stay of children, counseling centers of various kinds, groups for the supervision and care of preschool children ages organized by individual entrepreneurs. The article provides a grouping of municipalities by the effectiveness of the provision of public services of preschool education. The article also analyzes the results of the implementation of the national project "Demography", one of the directions of which is the creation of additional places in preschool educational institutions for children under the age of 3 years. Positive factors in the development of the market for preschool services are the presence of a private business and the creation of private preschool educational organizations in the region, the creation of groups for the supervision and care of preschool children organized by individual entrepreneurs. Important for the Far North region is the creation of groups of short-term stay of children in municipal organizations. The analysis shows the activity of government bodies in creating consultation centers for methodological, psychological, pedagogical, diagnostic and advisory assistance to parents in the education and upbringing of preschool children, centers for play support, leisure activities, weekend groups, parent-child club, groups for children disabled people. Digitalization of public administration is implemented through the creation of a regional electronic register of children in need of places in preschool educational institutions of the Komi Republic, which provides the possibility of a "transparent" procedure for the provision of services for receiving applications, registering and enrolling children in preschool educational organizations in electronic form.